The Impact of COVID-19 Disease on Platelets and Coagulation - Wool, Geoffrey D. (Pathobiology, 2020)
Coronavirus disease 2019 (COVID-19) causes a spectrum of disease; some patients develop a severe proinflammatory state which can be associated with a unique coagulopathy and procoagulant endothelial phenotype. Initially, COVID-19 infection produces a prominent elevation of fibrinogen and D-dimer/fibrin(ogen) degradation products. This is associated with systemic hypercoagulability and frequent venous thromboembolic events. The degree of D-dimer elevation positively correlates with mortality in COVID-19 patients. COVID-19 also leads to arterial thrombotic events (including strokes and ischemic limbs) as well as microvascular thrombotic disorders (as frequently documented at autopsy in the pulmonary vascular beds). COVID-19 patients often have mild thrombocytopenia and appear to have increased platelet consumption, together with a corresponding increase in platelet production. Disseminated intravascular coagulopathy (DIC) and severe bleeding events are uncommon in COVID-19 patients. Here, we review the current state of knowledge of COVID-19 and hemostasis.